Analisis Strategi Meningkatkan Minat Masyarakat Seberang Kota Jambi Terhadap Bank Syariah - Ayu Marta; Lucky Enggrani Fitri; Paulina Lubis (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
This research aims to determine the factors causing the low of interest of the people of Seberang Jambi City towards Sharia Banks, to find out and analyze opportunities, challenges and strategies that can be implemented to increase the interest of the people of Seberang Jambi City. This research uses a qualitative approach. The data source used in this research is primary. Data collection techniques were carried out using observation, interviews and documentation methods. The data analysis technique used in this research is SWOT analysis. The results of this research show that there are 2 factors causing the low interest of the people of Seberang Jambi City, namely internal and external factors. Internal factors namely; work encouragement factors, social environment encouragement and trust. Meanwhile, external factors causing the low interest of people across Jambi City in Sharia Banking are; Sharia Bank knowledge and products, promotion and outreach, location and facilities. The strategy to increase the interest of the people across Jambi City in Syariah Banking is to carry out regular outreach about sharia banking products, collaborate with all Islamic boarding school institutions across Jambi City, promote through distributing brochures and social media, and increase ATMs at strategic points .